Nutritional status, dietary practices and learning stimuli of selected public and private elementary pupils as correlated to academic achievement - Idaosos, Merlina G.
This study was conducted to determine the differences in the nutritional status, dietary practices and learning stimuli between public and private school elementary pupils. The study also determined the relationships between academic achievement and nutritional status as well as dietary practices and learning stimuli while considering the moderator variables: age, sex, type of school, and parents' educational attainment. The respondents were two hundred fifty nine (259) female and male Grade VI elementary school pupils aged 11-13 from public and private elementary schools in District II, Silang, Cavite. Random sampling was utilized in the selection of the schools from the six barangays of District II, Silang. The total number of respondents that were covered in the study were determined by complete enumeration of 259 Grade VI elementary pupils. The data gathering instrument was a survey questionnaire. It was developed by the researcher, validated by experts and pre-tested among 40 respondents chosen at random and who were not among the research respondents. It consisted of four parts of combined checklist and the anthropometric measurement. The questionnaire solicited information on the respondents' dietary practices, learning stimuli, and nutritional status that included weight-for-age, height-for-age and weight-for-height factors. The T-test analysis was used to determine the differences between public and private school pupils in terms of their dietary practices and learning stimuli. Results showed that there was higher prevalence of underweight in public schools (10%) than private schools (0.4%); while higher prevalence of overweight in private schools (20.8%) than in public schools (6.6%); the height-for-age between public (4.6%) and private schools (3.5%) had no significant difference. There was higher prevalence of underweight-for-age in public schools (11.56%) compared to private schools (2.7%). Overweight-for-height was shown to be prevalent in the private schools (19.3%) than in public schools (6.66%). Findings also showed there were differences in the learning stimuli between private and public elementary pupils in terms of environmental, emotional, sociological, psychological and physical stimuli. Results showed that environmental stimuli of private school pupils had a mean of 3.84 which is significantly higher than public school pupils with a mean of 3.66. Results also showed that the emotional learning stimuli of private school pupils had a mean of 4.05 which is significantly higher than public school pupils which has mean of 3.71. Findings also indicated that the physical learning stimuli of both private and public pupils showed no significant difference using independent T-Test. Stepwise regression analysis was used to determine the relationship between academic achievement to nutritional status, dietary practices, and learning stimuli. Based on the results, the dietary practices (specifically food variety and other dietary practices) and learning stimuli (specifically physical, sociological and psychological) were significant factors towards the academic achievement of the pupils. The study advanced programmatic recommendations for improving academic achievement of public and private school pupils considering the role of nutritional status, dietary practices and learning stimuli. The study also proposed the conduct of similar studies on bigger sample using randomized research designs.